HUBUNGAN TINGKAT KEPUASAN DAN KEPERCAYAAN PASIEN TERHADAP MUTU PELAYANAN KESEHATAN - Awaluddin Awaluddin; Seprian Budi Darma (LPPM Universitas Abdurrab, 2024)
ABSTRACK Quality service is one aspect of health services and is a key factor in achieving patient satisfaction. The existence of good service quality in an institution will create satisfaction for its patients. Patient trust in the quality of health services can judge the good services provided by government health facilities. The purpose of this study was to determine the relationship between the level of satisfaction and trust of patients with the quality of service at the Simpang Tiga Health Center in Pekanbaru City. This study uses the Cross Sectional method. The time of the study was 28 June-07 August 2023, with a population of 21,716 and the sample was determined by the Accidental Sampling method of 96 respondents. Data collection was carried out using a questionnaire. Analysis was performed by univariate analysis and bivariate analysis using the chi square test. The results of the correlation test for the relationship between the level of satisfaction and the quality of health services obtained a p value of 0.000 <0.005, so Ha1 was accepted, while the results of the correlation test for the relationship between trust and quality of health services obtained a p value of 0.000 <0.005, so Ha2 was accepted. So it can be concluded that there is a relationship between the level of satisfaction and trust of patients for the quality of health services at the Simpang Tiga Health Center, Pekanbaru City. It is hoped that this can be used as input for the Health Center to improve the quality of services provided to the community, especially health insurance services.